(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Developing customer satisfaction is regarded as being the highest possible priority for business success. Therefore, it’s important to determine the variables that influence customer satisfaction. In the casual restaurant sector of the Philippine market, this paper will examine whether product quality, pricing equality, and product discounts impact customer satisfaction. The results showed that for a casual restaurant’s good service to generate brand loyalty, its primary focus should be on product quality compared to pricing, especially regarding taste, freshness, and value. The results also showed that environmental factors and price fairness significantly increase consumer contentment. These findings offer policymakers in casual industry restaurants useful suggestions and recommended procedures. Food is an essential factor that the world needs the most. It has a great effect from a macro perspective to a micro perspective point of view. It is needed in able for the economy to have revenues from exportation to transactions inside a country’s premises, and it is also needed for every family in order for them to survive in their everyday lives. The major effect of food prices in the market is the inflation rate.